Paradigm Shift: Analyzing Work-Family Conflict Trends with Bibliometric Analysis and Literature Review Highlighting the Future Role’s of Father - Fauziah, Silmi Farhah; Abdullah, Ade Gafar; Widiaty, Isma (Journal of Vocational Education Studies, 2024)
Work-family conflict (WFC) is an important area of study in the vocational and human resources professions. This article investigates the complex dynamics of work-family conflict, with a particular focus on the developmental role of fathers in balancing professional responsibilities and family duties. This research uses bibliometric analysis methods and literature reviews to analyze the dynamics, research activities, and trends in research topics related to work-family conflict in a more comprehensive namely from 1985 to 2023. This research uses the keywords "work-family balance" OR "work-family conflict" OR "work-family intervention" and uses the Scopus database as the ideal data source for this research. Documents were visualized with VOSviewer and Tableau Desktop software to perform bibliometric analysis on publications, citations, and keywords. A literature review was also carried out regarding research objects, future work, and research gaps in areas that have not been touched by work-family conflict research, especially regarding the role of fathers in work and family life. December 6, 2023, 4405 documents from various types of scientific papers. Research findings show that in the last 38 years, there has been a significant increase in the number of publications discussing work-family conflict. The United States is the most productive country in publishing research related to work-family conflict. Keyword analysis shows that work-family conflict research focuses on the topics of father involvement, work-family balance, and gender. Future research should focus on exploring the impact of corporate policies, demographics, technology, and fatherhood, aiming to develop comprehensive workplace regulations that promote a balanced work-family environment.